Study guides

☆☆

Q: -2x2 plus 50 equals 0

Write your answer...

Submit

Still have questions?

Related questions

-7

3

x3 + 2x2 - 8x + 5 = 0 x(2x - 8) + 5 = 0

The discriminant is -199.

The discriminant is 25.

22 = 4

8 - 2x2 = x + 22 - 7Combine like terms on the right side:8 - 2x2 = x + 15Subtract 8 from each side:-2x2 = x + 7Add 2x2 to each side:0 = 2x2 + x + 7

x2 + 7x = 2x2 + 6 x2 - 2x2 + 7x = 6 -x2 +7x - 6 = 0 or alternatively x2 - 7x + 6 = 0

2x2 + 10 = 9x 2x2 - 9x + 10 = 0 (x - 2)(2x - 5) = 0

2x2+6x-8 = 72 2x2+6x-8-72 = 0 2x2+6x-80 = 0 (2x-10)(x+8) = 0

-50 plus 50 equals 0

If: 2x2-3x+1 = 0 Then: x = 1 or x = 1/2

The discriminant is 1.

2x2 + 10 - 9x = 0 or 2x2 - 9x + 10 = 0 So (x - 2)*(2x - 5) = 0

(2x + 1)(x + 3) = 0; x = -0.5 or -3

2x2+1x-3=0 4+x-3=0 x+1+0 x=-1 is your final answer

2x2+18x = 20 2x2+18x-20 = 0 x2+9x-10 = 0 (x+10)(x-1) = 0 x = -10 or x = 1

Since there is nothing "following" the answer is none of them.

x = (-1 ± √11) / 2

2x2 + 7x = 0 => x(2x+7)=0 so x = 0 or 2x+7 = 0 ie x = 0 or x = -7/2

2x2-7x+3 = 0 (2x-1)(x-3) = 0 x = 1/2 or x = 3

2x2+5x-3 = 0 (2x-1)(x+3) = 0 x = 1/2 or x -3

x = -1/2 or -5 2x2 + 11x + 5 = 0 ⇒ (2x + 1)(x + 5) = 0 ⇒ (2x + 1) = 0 → x = -1/2 or (x + 5) = 0 → x = -5

(2x - 1)(x - 1) so x = ½ or 1

50 - 40 = 10 + 0